Efektivitas Pelayanan Kartu Tanda Pencari Kerja Pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Kolaka Utara - Mirayanti Jihad, Andi Indah; Nurdin, Mochamat; AB, Fitrawati (JCOMENT (Journal of Community Empowerment), 2025)
The government is responsible for providing public service, but sometimes these service do not satisfy the public. Seeing that the services provided by the government are not yet optimal, a study was conducted on the effectiveness of the job seeker card (Ak-1) service provided by the Manpower and Transmigration Service of North Kolaka Regency. The purpose of this study was to analyze the effectiveness of the Ak-1 card service and to determine the determinant factors in the Ak-1 card service at the Manpower and Transmigration Service of North Kolaka Regency. This research method is qualitative research. Data collection techniques use observation and in-depth interviews. Data analysis techniques from Miles and Huberman is data collection, data reduction, data display, and conclusing drawing/ verification. The results of the study indicate that: (1) The effectiveness of the job seeker card (Ak-1) service at the Manpower and Transmigration Service of North Kolaka Regency has not been running effectively. (2) The determinant factors in the Ak-1 card service are internal factors of the availability of adequate facilities and infrastructure and the quality of information systems and technology, while external factors are government policies and community involvement and participation in the process of socializing the Ak-1 card service. This research is expected to broaden insight and be used as study material in compiling policies or regulations releted to Ak-1 card services in the context of service effectiveness, improving service quality and development of the Ak-1 service card system Siapkerja Application.